European economic integration - McDonald, Frank; Dearden, Stephen (London : Longman, 1992)
With its clear and accessible style and its combination of theory and applications, European Economic Integration will enable students to understand the European Community and place it in economic and historic context. The book focuses principally on the economic dimension of the EU, but places this firmly within the context of the surrounding political debates. Much has changed in the European Union since the publication of the third edition with the successful launch of the Euro and the accession of ten new member states. The 4th edition has been comprehensively revised to reflect these changes, providing up-to-date-coverage of the most important issues facing European economies in the 21st Century. Assuming only an introductory knowledge of economics and with its comprehensive coverage of EU economic policies, European Economic Integration is ideally suited to all students taking courses on the economics of the EU as part of an economics, business studies or inter-disciplinary European studies degree.
Includes bibliographical references and index.
lje 23/08/2016
Loans
Keywords: International economic relations; Economic integration; European Economic Community countries